Aseptic meningitis after 20 years of endoscopic transsphenoidal pituitary surgery: a rare complication - Hussain, Syed Zohaib Maroof; Anwer, Muhammad Osama; Noor, Syeda Marsha; Hashmi, Salman; Anwer, Sanam; Yaqoob, Uzair (Medicine and Pharmacy Reports, 2021)
A transsphenoidal surgical (TSS) approach is used for pituitary gland surgery involving pituitary adenomas, as well as for the biopsy of various neurosurgical tumors. TSS, although a relatively safe procedure, can lead to complications like hypopituitarism, visual impairment, nasal septal perforation, diabetes insipidus, carotid artery injury, and cerebrospinal fluid (CSF) leaks. Aseptic meningitis is also one of the complications of this procedure with an incidence of 1-2%, presenting with symptoms similar to bacterial meningitis, but with a low-grade fever of <102 F or even apyrexia. Here, we present a rare case of aseptic meningitis due to CSF leakage, presenting after 20 years of endoscopic surgery. A ventriculoperitoneal shunt was placed to stem the leak after two unsuccessful attempts of endonasal repair.